Human recombinant Fab fragment from combinatorial libraries of a B-cell lymphoma patient recognizes core protein of chondroitin sulphate proteoglycan 4. (28th September 2017) - Egami, Yoko; Narushima, Yuta; Ohshima, Motohiro; Yoshida, Akira; Yoneta, Naruki; Masaki, Yasufumi; Itoh, Kunihiko
Abstract: CD antigens are well known as therapeutic targets of B-cell lymphoma. To isolate therapeutic antibodies that recognize novel targets other than CD antigens, we constructed a phage display combinatorial antibody Fab library from bone marrow lymphocytes of B-cell lymphoma patient. To eliminate antibodies reactive with known B-cell lymphoma antigen, non-hematopoietic and patient's sera reactive HeLaS3 cells was selected as a target of whole cell panning. Five rounds of panning against live HeLaS3 cells retrieved single Fab clone, termed AHSA (Antibody to HeLa Surface Antigen). Using phage display random peptide library, LSYLEP was identified as an epitope sequence of AHSA. LC-MS/MS analysis of AHSA-precipitated HeLaS3 cell lysates detected several fragments corresponding to the sequence of chondroitin sulphate proteoglycan 4 (CSPG4) core protein. Since LSYLEP sequence was at the position of 313–318 of CSPG4, we considered that CSPG4 was AHSA-associated antigen. Double staining of CSPG4-postive MDA-MB-435S cells with AHSA and anti-CSPG4 rabbit antibody showed identical staining position, and reduced AHSA reactivity was observed in CSPG4-siRNA treated MDA-MB-435S cells. In conclusion, we retrieved a human Fab from antibody library of B-cell lymphoma patient, and identified CSPG4 as a recognizing antigen. AHSA may have potential benefits for development of CSPG4-targeting theranostics for B-cell lymphoma.